2013
DOI: 10.1016/j.brainres.2013.01.046
|View full text |Cite
|
Sign up to set email alerts
|

A ketogenic diet improves motor performance but does not affect β-amyloid levels in a mouse model of Alzheimer's Disease

Abstract: β-Amyloid (Aβ), a small, fibrillogenic peptide, is known to play an important role in the pathogenesis of Alzheimer’s disease (AD) in the brain. In addition, Aβ accumulates in skeletal muscle cells in individuals with sporadic inclusion body myositis (sIBM), an age-related muscle disease. Because of the socioeconomic burden associated with age-related diseases, particularly AD, there has been considerable emphasis on studying potential therapeutic strategies. The high fat, low carbohydrate ketogenic diet has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 30 publications
(42 reference statements)
4
59
0
Order By: Relevance
“…Other studies showed similar results; KD improved rotarod performance in young (1-2 month) nontransgenic and APP+PS1 mice when fed KD for one month [69], while no effects on the soluble amyloid in the brain or muscle could be detected by ELISA, similarly to the previous study [66].…”
Section: Metabolic Therapies In Mouse Models Of Alzheimer`s Diseasesupporting
confidence: 81%
“…Other studies showed similar results; KD improved rotarod performance in young (1-2 month) nontransgenic and APP+PS1 mice when fed KD for one month [69], while no effects on the soluble amyloid in the brain or muscle could be detected by ELISA, similarly to the previous study [66].…”
Section: Metabolic Therapies In Mouse Models Of Alzheimer`s Diseasesupporting
confidence: 81%
“…However, patient compliance on ketogenic diets is challenging owing to its high fat and low carbohydrate content. In addition, there are studies indicating that ketone bodies have little effect on AD pathology, despite benefits on motor performance [57,66]. Two early proof-of-concept clinical studies, investigating ketone bodies for mild-to-moderate AD, reported significant improvements on multiple measures of cognition [58,59].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
“…This is based on studies with victims of severe brain injury or mouse models. The latter show that ketogenic diets impact the tau protein associated with Alzheimer's disease plaques, in some but not all studies, and improve motor activity, but not cognition (17,18,35,36). Such studies also show that excess calorie intake or high-CHO diets impair not only the formation of brain-derived neurotrophic factor, but also its signaling in the hippocampus, which is critical for memory (37).…”
Section: Carbohydrates and Vitamins From Grains And Their Relationshimentioning
confidence: 93%